Revisiting imaging features of rectosigmoid vascular malformation with emphasis on multiparametric MRI: a case report - Erdemli, S.; Alis, D.; Cicek, B.; Goksel, S.; Karahasanoglu, T.; Karaarslan, E. (SPRINGER, 2022)
Background: Gastrointestinal vascular malformations are rare benign vascular neoplasms of the gastrointestinal tract, with the rectosigmoid region being the most frequently involved site. Patients often manifest with recurrent, intermittent rectal bleeding, which might occasionally be life-threatening. Case presentation: A 39-year-old man with a history of hemorrhoid operations twice was presented to our gastroenterology department with blood in the stool and abdominal pain. After the colonoscopy, multiparametric MRI, and CT examinations, robotic low anterior resection was performed with the diagnosis of rectosigmoid venous malformation. The histopathological examination confirmed the diagnosis. Conclusion: Colonoscopy is the preferred method in diagnosing rectosigmoid vascular malformation, but wrong and delayed diagnoses are common.Thus, imaging modalities might add to colonoscopy in equivocal cases.
Keywords: Magnetic resonance imaging; Rectum; Vascular anomalies; Colonoscopy; Hemangioma